(untitled) (Journal of Forensic Medicine & Toxicology, 2020)
Since time immemorial the doctor patient relationship relied on the mutual trust and conviction. However, over the years owing to the commercialization of the health care and the medical profession, the profession ran out of faith. Inclusion of medical services under the purview of Consumer Protection Act, in 1995, further transformed the relationship between a doctor and patient from a very trusting kind to mere contractual. Thus it has become imperative for all modern day medical professionals to have a comprehensive knowledge of Consumer Protection Act and its implications in their profession. In this very light the current research work is an attempt to assess the awareness of undergraduate medical students towards Consumer Protection Act.